Social implications of a change in the legal classification of COVID-19: The need for pandemic prevention, preparedness, and healthcare system strengthening - Ohmagari, Norio (Global Health & Medicine, 2023)
In Japan, there has been a discussion of the potential reclassification of the novel coronavirus infectious disease 2019 (COVID-19) as an infectious disease under the Act on the Prevention of Infectious Diseases and Medical Care for Patients with Infectious Diseases (the Infectious Diseases Control Law), beginning in late 2022. To make an informed decision, the societal impact of COVID-19 needs to be carefully considered to ensure that any reclassification does not negatively impact healthcare or society as a whole. The disease burden of COVID-19 remains considerable and is likely to persist for an extended period of time. Consequently, numerous special measures have been taken in the healthcare system to cope with COVID-19. Several of these measures must be implemented. Thus, the healthcare system needs to be strengthened in the future. This will result in adequate prevention, preparation, and a response to future pandemics.